Manuaba waterfall marketing strategy as a spiritual tourism attraction in Kenderan Tourism Village, Gianyar regency - Ni Wayan Wina Premayani; Putu Herny Susanti; Made Dian Putri Agustina (Enrichment : Journal of Management, 2022)
Tourism marketing is a management process that coordinates companies that are members of the tourism service industry to provide services and communications with the aim of satisfying tourists' desires within a local, regional, national or international scope. Manuaba waterfall is a natural tourist attraction, which is currently visited by tourists with the aim of carrying out spiritual tourism activities. In service/hospitality marketing, it is known that there is the term 8 P's of marketing. The marketing mix in hospitality consists of: product, price, place, promotion, people, packaging, programming, and partnership, (Morrison, 2010; 351). The purpose of this research is to increase the attractiveness of spiritual tourism in Manuaba waterfall and determine the right marketing strategy for Manuaba waterfall. The theories in this study are the 8 P's theory, 4A theory and the Tourism Area Life-Cycle (TALC) theory. This study uses a qualitative method through in-depth interviews with relevant stakeholders/stakeholders and academics. From the potential for spiritual tourism, the Manuaba waterfall has natural beauty and an aura of mysticism that makes people who visit feel calm, comfortable and connected to the creator. From the 4A analysis, we can see that the Manuaba waterfall is starting to develop into a spiritual tourism attraction. Manuaba waterfall currently based on TALC (tourism area life cycle) is on exploration. At this stage there is a high interaction between the community and tourists. The position of the Manuaba waterfall, which is currently in an exploration position, must be introduced to its existence, especially as a spiritual tourism attraction through marketing promotions.